Pendugaan potensi kandungan karbon pada tegakan jati (Tectona grandis LINN. F) di areal KPH Cianjur perum perhutani unit III Jawa Barat dan Banten - Thea Catleya Agnita; Bambang Hero Saharjo (Institut Pertanian Bogor, 2011)
The land use and land use change through forest conversion and also the increasing heavy industry which produce high value of pollutant had bad impact to the environment which finally affect the global climate change. The importance of vegetation in the forest which have a role to reduce green house gass through fotosintetic became important, then the focus of this research was to know the carbon stock of certain vegetation especially teak, in KPH Cianjur PERHUTANI UNIT III Wesat Java and Banten. The research done in the period of April 2010 until may 2010 in the KPH Cianjur, PERHUTANI UNIT Ill Wesat Java and Banten. The materials used for this study which teak plantation planted in the year 1997 and 1990. The step taken for the research content of establishing and making of research site estimating biomass stand, sampling of litter and understory. The result of research shown that the carbon stock of teak plantation which spacing 3 x 2 m at 1997 planting year was 73.519 ton/ha, while at 1990 planting year was 93.94 ton/ha. It means that the carbon stock of teak planted in the year 1990 was bigger than in the year 1997.